SIRT1/2 orchestrate acquisition of DNA methylation and loss of histone H3 activating marks to prevent premature activation of inflammatory genes in macrophages. Issue 2 (4th December 2019) - Li, Tianlu; Garcia-Gomez, Antonio; Morante-Palacios, Octavio; Ciudad, Laura; Özkaramehmet, Sevgi; Van Dijck, Evelien; Rodríguez-Ubreva, Javier; Vaquero, Alejandro; Ballestar, Esteban
Abstract: Sirtuins 1 and 2 (SIRT1/2) are two NAD-dependent deacetylases with major roles in inflammation. In addition to deacetylating histones and other proteins, SIRT1/2-mediated regulation is coupled with other epigenetic enzymes. Here, we investigate the links between SIRT1/2 activity and DNA methylation in macrophage differentiation due to their relevance in myeloid cells. SIRT1/2 display drastic upregulation during macrophage differentiation and their inhibition impacts the expression of many inflammation-related genes. In this context, SIRT1/2 inhibition abrogates DNA methylation gains, but does not affect demethylation. Inhibition of hypermethylation occurs at many inflammatory loci, which results in more drastic upregulation of their expression upon macrophage polarization following bacterial lipopolysaccharide (LPS) challenge. SIRT1/2-mediated gains of methylation concur with decreases in activating histone marks, and their inhibition revert these histone marks to resemble an open chromatin. Remarkably, specific inhibition of DNA methyltransferases is sufficient to upregulate inflammatory genes that are maintained in a silent state by SIRT1/2. Both SIRT1 and SIRT2 directly interact with DNMT3B, and their binding to proinflammatory genes is lost upon exposure to LPS or through pharmacological inhibition of their activity. In all, we describe a novel role for SIRT1/2 to restrict premature activation of proinflammatory genes.